Sahnun’s Religious-Conservative Educational Thought and Its Relevance to Contemporary Pesantren Education: A Systematic Literature Review - Kusno, Moh.; Vangga, Trio; Abu Bakar , M. Yunus; Mas'ud, Ali (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
Sahnun’s religious-conservative thought, as articulated by a prominent ninth-century Maliki jurist, made a significant contribution to preserving Islamic orthodoxy through his monumental work al-Mudawwanah al-Kubrā. This intellectual orientation emphasizes strong adherence to authoritative religious texts, the authority of the ulama, and the strict implementation of Islamic legal practices. Meanwhile, pesantren in Indonesia are widely recognized as traditional Islamic educational institutions that prioritize discipline, obedience to scholarly authority, and the embedding religious character. The intersection between Sahnun’s conservatism and the pesantren tradition therefore warrants closer scholarly examination. The central research question of this study concerns how Sahnun’s religious-conservative thought is understood and the extent to which it is relevant to the pesantren educational system. This study employs a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Data were drawn from 21 Scopus-indexed journal articles published between 2015 and 2025. The selection process involved identification, screening, eligibility assessment, and the synthesis of relevant findings. The results indicate that key elements of Sahnun’s religious conservatism, such as textual authority, fiqh discipline, and a firm commitment to preserving tradition, exhibit strong resonance with contemporary pesantren education. This study affirms that Sahnun’s conservatism not only played a crucial role in the historical development of Islamic law but also provides a normative and epistemological foundation for the continuity of pesantren as Islamic educational institutions in the contemporary era.